Clinical application status of wax therapy and nursing measures (蜡疗技术的临床应用现状及护理) - LI Nan (李楠); LI Suqian (李苏茜) (中西医结合护理)
With advantage of obvious curative effect, easy-to-operate process, convenient in practice and less adverse reactions, wax therapy is proven to be effective to relieve symptoms of multiple diseases. This paper reviewed studies on principle, mechanism and clinical application of wax therapy, as well as nursing measures during treatment, and provided reference for researches on standardization and practice of Traditional Chinese Medicine was therapy technique. (中药蜡疗具有疗效确切、操作简便、方便实用、不良反应少等优势, 在缓解诸多疾病症状方面具有较好的效果。本研究就蜡疗的作用原理、蜡疗在临床中的应用现状以及蜡疗相关的护理对策进行总结分析, 从而为临床中进一步研究中药蜡疗技术的规范性和可操作性提供依据。)